2020
DOI: 10.3354/ame01928
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic variations of picophytoplankton in three contrasting seas: the Bay of Bengal, South China Sea and Western Pacific Ocean

Abstract: Marine picophytoplankton are abundant in many oligotrophic oceans, but the known geographical patterns of picophytoplankton are primarily based on small-scale cruises or time-series observations. Here, we conducted a wider survey (5 cruises) in the Bay of Bengal (BOB), South China Sea (SCS) and Western Pacific Ocean (WPO) to better understand the biogeographic variations of picophytoplankton. Prochlorococcus (Pro) were the most abundant picophytoplankton (averaging [1.9-3.6] × 104 cells ml-1) across the 3 seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 49 publications
4
21
1
Order By: Relevance
“…In accordance with our finding, studies reveal that Synechococcus accumulated higher than Prochlorococcus and picoeukaryotes in tropical and equatorial ocean from surface waters down to the base of thermocline (Partensky et al, 1999a;Mena et al, 2019;Pan et al, 2007). Contrastingly, some studies found Prochlorococcus to be more abundant than Synechococcus in the North Atlantic, South Pacific, North Indian basins (Buitenhuis et al, 2012), the subtropical and tropical ocean (Agusti et al, 2019;Chen et al, 2009), including south China Sea (Jiang & Sun, 2020;Wei et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In accordance with our finding, studies reveal that Synechococcus accumulated higher than Prochlorococcus and picoeukaryotes in tropical and equatorial ocean from surface waters down to the base of thermocline (Partensky et al, 1999a;Mena et al, 2019;Pan et al, 2007). Contrastingly, some studies found Prochlorococcus to be more abundant than Synechococcus in the North Atlantic, South Pacific, North Indian basins (Buitenhuis et al, 2012), the subtropical and tropical ocean (Agusti et al, 2019;Chen et al, 2009), including south China Sea (Jiang & Sun, 2020;Wei et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that Synechococcus are the most successful group among the picophytoplankton in Pahang coastal waters (Station 1a, 2b, Figure 4) where we would expect an influence of the nutrient derived from the riverine and the aquaculture area output to this area, as indicated in Shaari et al (2013). Nevertheless, several studies could not find a clear relationship between nutrient concentration and cell abundance of picophytoplankton (Flombaum et al, 2013;Guo et al, 2014;Mouriño-Carballido et al, 2016;Wei et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations